Human perception and machine vision reveal rich latent structure in human figure drawings - Jensen, Clint A.; Sumanthiran, Dillanie; Kirkorian, Heather L.; Travers, Brittany G.; Rosengren, Karl S.; Rogers, Timothy T. (Frontiers in Psychology, 2023)
For over a hundred years, children’s drawings have been used to assess children’s intellectual, emotional, and physical development, characterizing children on the basis of intuitively derived checklists to identify the presence or absence of features within children’s drawings. The current study investigates whether contemporary data science tools, including deep neural network models of vision and crowd-based similarity ratings, can reveal latent structure in human figure drawings beyond that captured by checklists, and whether such structure can aid in understanding aspects of the child’s cognitive, perceptual, and motor competencies. We introduce three new metrics derived from innovations in machine vision and crowd-sourcing of human judgments and show that they capture a wealth of information about the participant beyond that expressed by standard measures, including age, gender, motor abilities, personal/social behaviors, and communicative skills. Machine- and human-derived metrics captured somewhat different aspects of structure across drawings, and each were independently useful for predicting some participant characteristics. For example, machine embeddings seemed sensitive to the magnitude of the drawing on the page and stroke density, while human-derived embeddings appeared sensitive to the overall shape and parts of a drawing. Both metrics, however, independently explained variation on some outcome measures. Machine embeddings explained more variation than human embeddings on all subscales of the Ages and Stages Questionnaire (a parent report of developmental milestones) and on measures of grip and pinch strength, while each metric accounted for unique variance in models predicting the participant’s gender. This research thus suggests that children’s drawings may provide a richer basis for characterizing aspects of cognitive, behavioral, and motor development than previously thought.